Lateralisation of language functions in the brain: Effects of handedness - O'Regan, Louise (2020)
Evidence suggests that an individuals’ handedness is intrinsically linked to their brain asymmetry for speech and language functions. The best estimates suggest that the left hemisphere is dominant for language in 95% of right-handers and 70-85% of left-handers. Atypical or reversed language laterality patterns have been observed in 4% of strong right-handers and up to 27% of strong left-handers, which points to increased variability due to non-right-handedness and confirms that handedness is a useful tool to study individual differences in brain organisation.